2001
DOI: 10.1006/viro.2001.1003
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Targeting of the Coat Protein of African Cassava Mosaic Geminivirus

Abstract: The coat protein (CP) of geminiviruses is involved in a number of processes during the life cycle of the virus. The predominant function is encapsidation of single-stranded DNA and formation of the virus particle to protect viral DNA during transmission. The CP of monopartite geminiviruses is absolutely essential for virus movement, whereas CP mutants of bipartite geminiviruses are able to infect some host plants systemically, indicating an involvement of the CP in host specificity. During the life cycle of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 44 publications
2
44
0
2
Order By: Relevance
“…The basic domains in the CP N-terminal region form an essential part of the NLS in Old World viruses and their C. Ha and others role in nuclear targeting has been demonstrated for TYLCV (Kunik et al, 1998), ACMV (Unseld et al, 2001) and MYMV (Guerra-Peraza et al, 2005). The reason for the absence of these domains in New World viruses is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic domains in the CP N-terminal region form an essential part of the NLS in Old World viruses and their C. Ha and others role in nuclear targeting has been demonstrated for TYLCV (Kunik et al, 1998), ACMV (Unseld et al, 2001) and MYMV (Guerra-Peraza et al, 2005). The reason for the absence of these domains in New World viruses is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3. DBasic domains of the nuclear-localization signals (Guerra-Peraza et al, 2005;Kunik et al, 1998;Unseld et al, 2001) are shown in bold. The 7-PWRsMaGT motifs (Harrison et al, 2002) are underlined.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…For the ACMV CP, three regions have been determined that mediate nuclear import (Unseld et al, 2001), whereby the central region is not only important for nuclear import but also for export. Deletions within these regions, which may overlap with DNA binding and multimerization regions, inhibited the formation of virus particles .…”
Section: Introductionmentioning
confidence: 99%
“…The single CP possesses a molecular mass of 30.1 kDa and a calculated pI of 10.0. Each geminate particle encapsidates one circular DNA molecule so that two virions are needed for infection in case of bipartite geminiviruses.Encapsidating the viral genome, the geminivirus CP is important for insect transmission (Briddon et al, 1990; Höfer et al, 1997; Höhnle et al, 2001;Kheyr-Pour et al, 2000; Noris et al, 1998) and transport of the viral DNA in and out of the nucleus (Kotlizky et al, 2000;Kunik et al, 1998Kunik et al, , 1999 Liu et al, 1999;Unseld et al, 2001Unseld et al, , 2004. For the ACMV CP, three regions have been determined that mediate nuclear import (Unseld et al, 2001), whereby the central region is not only important for nuclear import but also for export.…”
mentioning
confidence: 99%
“…Both CP and NSP are targeted to the nucleus, and at least NSP, hence its name, is able to shuttle between the nucleus and the cytoplasm (19,24,33,38,46,47,50). Protein domains responsible for DNA binding and intracellular localization have been analyzed for several geminiviruses.…”
mentioning
confidence: 99%